Cartography in the context of the Family Health Strategy: Ways possible from the georeferencing (Research, Society and Development, 2024)
Objective: to report the experience of a workshop about cartography in the context of the Family Health Strategy, which used georeferencing as a tool for organizing health work. Methods: This is a qualitative, descriptive, them experience report study, which took place in a municipality in Bahia, that involved 39 participants, with weekly meetings during the month of November 2021. We used the Problem Based Learning (PBL) and a moment of practice for each team based on the instruction manual Qualifica APS: Tutorial para georreferenciamento da APS através da ferramenta Google Maps. Results:  The workshop made it possible to work on concepts about territorialization in Primary Care, mapping, cartography and georeferencing, with criticism and reflections on the importance of teamwork, in an Interprofessional and collaborative perspective, which also allowed to stimulate the creativity of participants. Conclusion: The workshop revealed that the use of technology can be a barrier, but the development of collaborative work can bring lightness to the implementation of health work. It has clear that adopting the use of smart maps will provide a continuous process of updating the work in the Family Health Strategy.